Transformasi dan Integrasi dalam Kesusastraan Nusantara: Perbandingan Teks Amir Hamzah Melayu dan Jawa - Kun Zachrun Istanti (Humaniora, 2010)
The Persian Amir Hamzah text has been transformated either directly or indirectly into Arabic, Hindustani, Bengali, Turkish, and Malay. The Malays Amir Hamzah text is connector the Amir Hamzah text contained in the regional languages in Indonesia since the Malays language is the spreader of religion of Islam in Indonesia. In Indonesia, the Amir Hamzah text spread and became popular along with the spread of Islam. The Amir Hamzah text used to convey the Islamic teaching in its creation occurs through the distortion (i.e., modification, manipulation, and adjustment) with the teaching will be delivered. Various distortions are done, either for its Malay, or Javanese.